(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In this paper, results mainly on the structures of some special class of real valued functions on an interval are discussed. Two other signicant results are also established. These results have been derived and presented mainly in the perspective of study of relations between real valued functions and their derivatives. The results are very fundamental in nature and may be useful in the next course of generalizations or improvements in this direction.